Full vaccination coverage and associated factors among children aged 12 to 23 months in remote rural area of Demba Gofa District, Southern Ethiopia - Darebo, Tadele Dana; Oshe, Bahru Belachew; Diro, Chala Wegi (PeerJ, 2022)
Background Full vaccination refers to the administration of vaccines/antigens recommended for children in the first year of life. However, little is known about full vaccination in remote, rural Ethiopia. This study aimed to measure full vaccination coverage and associated factors among children aged 12 to 23 months in Demba Gofa District, Southern Ethiopia. Methods A community-based cross-sectional study was conducted in April and May 2019 using a multistage sampling technique to select 677 mothers with children 12–23 months of age. Data was collected using a pre-tested structured questionnaire, and data were edited, coded, entered, and cleaned using Epi Info v3.1 and analyzed using SPSS v20. Bivariate and multivariable logistic regression was used to understand associations between dependent and independent variables. Results Three-hundred and nine children (47.0%) were fully vaccinated, 274 (41.7%) were partially vaccinated, and 74 (11.3%) were not vaccinated at all. Children were more likely to be vaccinated if decisions were made jointly with husbands (AOR = 1.88, 95% CI [1.06–3.34]), were made by mothers (AOR = 4.03, 95% CI [1.66–9.78]), followed postnatal care (AOR = 5.02, 95% CI [2.28–11.05]), if the child’s age for completing vaccination was known (AOR = 2.54, 95% CI [1.04–6.23]), and if vaccinations did not make the child sick (AOR = 0.32, 95% CI [0.16–0.64]). Conclusion Full vaccination coverage was less than average in the study district and far below the governmental target (90%) necessary for sustained control of vaccine-preventable diseases. Interventions targeted towards maternal healthcare decision-making, postnatal care, knowledge on vaccination timing, and importance should be prioritized to improve full vaccination coverage. A continuous supply of vaccination cards needs to be ensured to improve vaccination conditions.
Keywords: Full vaccination; 12–23 months; Children; Demba Gofa District; Southern Ethiopia